PELATIHAN PENGGUNAAN MENDELEY UNTUK MANAJEMEN REFERENSI MAHASISWA STIKES AL-FATAH BENGKULU - Parwito, Parwito (Fakultas Pertanian, 2024)
Effective reference management is a crucial component in academic writing to ensure the accuracy and completeness of citations. However, many students at STIKES AL-FATAH Bengkulu face challenges in managing references, such as citation format errors and difficulties organizing source materials. To address these issues, this community service activity aims to provide training on the use of Mendeley as a reference management tool for students. We conducted the training using a participatory approach, which included lectures, discussions, and hands-on practice. We gave the participants, consisting of 30 students, an understanding of the basics of using Mendeley, including installation, library management, creating reference folders, and applying automatic citation formats in Microsoft Word. The participants themselves provided the computers for this one-day activity at the STIKES AL-FATAH Bengkulu campus. The results of the program showed that more than 90% of participants successfully mastered the basic skills of using Mendeley, as evidenced by their ability to compile bibliographies in the correct format. Additionally, most participants provided positive feedback on the training, stating that using Mendeley made the process of academic writing significantly easier for them.